Conditions and Edges for the Photochemical Generation of Short-Lived Aryl Cations: A Computational Approach - Raviola, Carlotta; Ravelli, Davide; Protti, Stefano; Albini, Angelo; Fagnoni, Maurizio (Synlett, 2015)
A DFT investigation on the conditions required for the photochemical generation of triplet aryl cations from differently para-substituted aryl halides has been carried out. The results showed a correlation between the energy change associated with the Ar–X bond heterolytic cleavage and the substituent Hammett–Brown constant (σp+). The method provides a means to predict the viability of the ArSN1 photosubstitution reaction.
Keywords: phenyl cations; metal-free arylation; photochemical activation; aryl halides; Hammett–Brown constants